Genetic Algorithm Based Palm Recognition Method for Biometric Authentication Systems - Cenys, A.; Gibavicius, D.; Goranin, N.; Marozas, L. (Elektronika ir Elektrotechnika, 2013)
Biometric authentication systems are steadily becoming a solution to wide number of authentication and identity management problems. Unique parts of human body that can be recognized and used as a mean to identify a person include fingerprints, iris, lips, etc. Though fingerprint and facial recognition systems are most widely used and developed, most of the systems and methods are slow or require expensive technical equipment. In this article genetic algorithm based palm recognition method is proposed, which does not require special equipment and can be used in systems where fast detection is needed. Method is compared to other existing methods. Method description, test results and evaluation are provided. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.3473